A Cross-Sectional Study Comparing Trendelenburg With Stripping And Radiofrequency Ablation For The Management Of Primary Varicose Veins In A Tertiary Care Setting In Tamil Nadu - Elangovan, Swathy; Thinagaran. K, Thinagaran. K; Subramania Nathan, Vivekananda; R. Sivamarieswaran, R. Sivamarieswaran; Jose .M, Reegan (Journal of Neonatal Surgery, 2025)
Introduction: Varicose veins are a common venous disorder characterised by venous dilation, tortuosity and valvular dysfunction primarily affecting the great saphenous vein (GSV). The condition leads to chronic venous hypertension, contributing to symptoms such as leg pain, heaviness, edema, and ulceration. While the Trendelenburg procedure with stripping has long been a standard surgical treatment, minimally invasive techniques like Radiofrequency Ablation (RFA) have gained prominence due to their advantages, including reduced postoperative pain and shorter recovery times. Despite its increasing adoption, comparative data evaluating RFA versus Trendelenburg with stripping in resource-limited settings remains limited. Aim: This study compares the clinical outcomes of the Trendelenburg procedure with stripping versus RFA in primary varicose vein treatment. Key parameters evaluated include procedure time, pain levels, hospital stay, complications, CEAP classification improvement, Venous Severity Score (VSS) and patient satisfaction. Materials and Methods: This cross-sectional comparative study was conducted over one year with 80 patients with lower limb varicose veins randomly assigned into two groups: Group A (Trendelenburg with stripping, n=40) and Group B (RFA, n=40). Patients aged 18 to 60 years, classified as ASA Grade I & II with C2 to C5 varicose veins, were included, while those with prior varicose vein surgery, deep vein thrombosis, or peripheral arterial disease were excluded. Postoperative assessments at 1 week and 1 month included procedure time, postoperative pain (VAS score), hospital stay, return to normal activities, complications, CEAP classification improvement, VSS and patient satisfaction. Results: Among 90 screened patients, 80 met eligibility criteria and were randomly assigned into two groups. RFA resulted in significantly shorter procedure times, lower postoperative pain, reduced hospital stays and a faster return to normal activities than the Trendelenburg with stripping group (p < 0.001). The complication rate was lower in the RFA group (7.5%) than in the Trendelenburg with stripping group (32.5%) (p = 0.005). Conclusion: The findings support the clinical advantages of RFA over the Trendelenburg procedure with stripping. RFA demonstrated reduced procedure times, lower postoperative pain, fewer complications and faster recovery making it a more efficient and patient-friendly treatment option.